Application of Circular Economy in Downstream Petroleum Industry: An Interpretative Modelling - Ahmad Ghorbanpur; Abdol Karim Hosseinpoor (Environmental Energy and Economic Research)
In recent years, globalization, the large consumption of resources, increasing pollution, and consequently, the production of waste and greenhouse gases created serious environmental problems. In this regard, the most important philosophy needed by organizations is agreement on creating economic, social and environmental value in the form of the concept of sustainable management. Circular economics is an operational solution to achieve this concept in organizations. This paper attempts to offer multi-level modeling of circular economy barriers in the downstream petroleum industry, emphasizing the rubber and plastics industry. In first, a number of the barrier are extracted from related reviews of the studies. Then, these barriers were validated using experts’ opinions in academic and petroleum industry professionals. Then, the fuzzy interpretative structural modeling approach (FISM) was used to determine the relationship between the barriers by considering the linguistic ambiguities of judgments and designing the structural model. The results showed that from the viewpoint of experts, due to the placement of “Obstructing laws and regulations” and “Uncertainty of consumer demand” barriers in the root of the model were the most important barriers of circular economy in the rubber and plastics industry. In the next step, using the MICMAC analysis, the circular economy barriers were put into four clusters. Finally, a discussion and conclusions are presented.